Crianças falam conforme o modelo mesmo quando consequências seguem falas divergentes - Souza, Rodrigo Dal Ben de (Universidade Federal de São Carlos, 2016)
The development and maintenance of vocal verbal repertories that follow structural regularities are processes in need for investigation under the selection by consequences paradigm. The present study investigates the effects of presenting vocal models in passive voice and explicit consequences, of high and medium preference, contingent to descriptions in active voice on the verbal voice of descriptions of Brazilian young children, 4 years old on average. Three experiments were performed. In the first, four children participated. The experimental procedure was composed by five conditions. In the first one, 10 drawings, with two animals interacting, were presented and its descriptions asked. In the second, experimenter and participant alternated in describing 20 drawings, the experimenter always described in passive voice. The third condition was similar to the second, except that descriptions in active voice (divergent) were followed by preferred consequences. The fourth condition was similar to the first one. The fifth condition was similar to the fourth, but it was conducted by an unknown experimenter. All participants described in passive voice after being exposed to the model and continued doing so even when preferred consequences followed descriptions in active voice. But the experimental design may have created a sequence effect between the second and the third conditions. Such limitation was followed in a second experiment. Other four young children participated, 4 years old on average. The procedure was similar to the first experiment, but, the model in passive voice during the second condition was replaced by the presentation of preferred explicit consequences contingent to active voice descriptions. All participants described in passive voice after being exposed to the model, except one. In order to refine the investigation, a third experiment was conducted. Other four young children mean of 4 years old, with different degrees of model following participated. The procedure was identical to the second experiment, but a pre-experimental condition was added in order to measure the participants’ sensibility to the model. Nevertheless, all participants described in passive voice after being exposed to the model in the third experimental condition. The findings point to the importance of investigations on non-arranged contingencies of reinforcement in the development and maintenance of verbal vocal repertoires that follow structural regularities.
Keywords: Regularidades estruturais; Comportamento verbal; Imitação; Quadros intraverbais; Structural regularities; Verbal behavior; Imitation; Intraverbal frames; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL